Industrial training report: INTEC Education College / Nurul Izreen Yasmin Istha’ @ Isha’ - Istha’ @ Isha’, Nurul Izreen Yasmin (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report is about internship experience at an education institution in INTEC Education College and it focused on Admission and Marketing department. The internship begins on 22nd July 2024 first in INTEC Urban campus at Bukit Jelutong before completely moving back in Section 17 Shah Alam. Throughout this internship, the experience working in an office and education institution has had an absolute impact on students as they quickly learn how working life in adulthood so that they can imply the experience and knowledge in future. It is concluded that industrial training is essential as it plays a role in developing and shaping the student’s capabilities for future usage.